2021
DOI: 10.1002/med.21790
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of microRNA‐208a in cardiology and reverse cardio‐oncology

Abstract: Cardiovascular diseases (CVDs) and cancer, which are the leading causes of mortality globally, have been viewed as two distinct diseases. However, the fact that cancer and CVDs may coincide has been noted by cardiologists when taking care of patients with CVDs caused by cancer chemotherapy; this entity is designated cardio‐oncology. More recently, patients with CVDs have also been found to have increased risk of cancers, termed reverse cardio‐oncology. Although reverse cardio‐oncology has been highlighted as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 139 publications
(225 reference statements)
0
5
0
Order By: Relevance
“…The next investigated markers are non‐coding RNAs. Wang et al's study revealed that an elevated level of microRNA‐208a can be a useful indicator of high risk in patients with HF and malignancy; however, its role in cardiotoxicity remains unclear 54 …”
Section: Pre‐treatment Screening Methodsmentioning
confidence: 99%
“…The next investigated markers are non‐coding RNAs. Wang et al's study revealed that an elevated level of microRNA‐208a can be a useful indicator of high risk in patients with HF and malignancy; however, its role in cardiotoxicity remains unclear 54 …”
Section: Pre‐treatment Screening Methodsmentioning
confidence: 99%
“…hypertension, heart failure (HF), arteriosclerosis (AS) and myocardial infarction (MI) etc.) can influence distant tumor development by secreting circulating factors, such as the noncoding RNA, cytokines and proteins [23,26,31]. The Cardio-miRNAs of cardiovascular dysfunction (e.g., pro-inflammatory and cellular senescence) is an important inducing factor for cardiovascular diseases.…”
Section: The Outness Of Cardio-mirnas Affecting Tumor Progression Via...mentioning
confidence: 99%
“…However, the role of miRNAs as a systemic influence in the synthesis of crosstalk between different diseases is still less. Especially, some typical biomarkers reflected by changes of expression profile for Cardio-miRNAs in circulation, which may become an important factor that diseases associated with age [26,30,173]. Therefore, Cardio-miRNAs may be keys to potential targets that treating chronic complications and malignant progression of tumor [30,174].…”
Section: Perspectives and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…These works demonstrated that miRs may be important regulators of various cardiovascular diseases and pathological processes in cancer. In-depth understanding of the role of miRs in reverse cardio-oncology is expected to "kill two birds with one stone" [315].…”
Section: Advances In Reverse Cardiac Oncologymentioning
confidence: 99%